Aquaculture of emerging species in North-Eastern Atlantic and Mediterranean Sea: a systematic review on sea cucumber farming and potential development - Ciriminna, Laura; Signa, Geraldina; Cilluffo, Giovanna; Rakaj, Arnold; Vizzini, Salvatrice (Frontiers in Marine Science, 2024)
Sea cucumbers are considered a traditional food delicacy in Asian countries. In last decades high market demand, uncontrolled exploitation and inadequate management have led to stock overexploitation, driving commercial interest in new target species and new areas. In recent years, Mediterranean and North-East Atlantic sea cucumbers have become fishing targets, and, due to overfishing, a significant decline of wild populations have been observed, with detrimental effects on benthic communities and ecosystems. Indeed, in addition to being an important economic resource, sea cucumbers play a key ecological role in benthic dynamics where they are involved as ecosystem engineers in the processing of organic matter in the detrital food web pathway. In this context, aquaculture can play a crucial role in supporting the conservation of natural stocks by reducing harvesting pressure on wild populations and enabling restoration programmes for depleted stocks. Commercial sea cucumber farming is already an established reality in the Indo-Pacific region, where it has become one of the most profitable sectors of aquaculture production. In Europe, on the other hand, sea cucumber aquaculture is still an emerging sector, whose development is hampered by poor and fragmented information on the farming requirements of native species. In this context, this systematic review was carried out with the aim of providing a comprehensive summary of the state of the art of farming practices of the European sea cucumbers considered as a target of commercial fisheries. A total of 34 original articles were included in this review, after title, abstract and full-text screening. The results highlighted a sharp increase in the number of studies over the last six years. Portugal, Turkey and Italy are the countries where most research has been carried out. Among the selected species, Holothuria tubulosa was the most studied, while only one article was found on Parastichopus regalis. The main aims of this review were i) to gather all available literature on the farming practices of North-East Atlantic and Mediterranean sea cucumber species, ii) to outline the most common farming practices, iii) to identify gaps and future directions in this emerging aquaculture sector.